The international dimension of European climate policy: A strategy for integrating the internal and external dimensions - Ole Adolphsen; Jule Könneke; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2025)
With the Green Deal, the European Union (EU) has not only significantly increased the ambition of its climate policy in recent years, but it has also added an international dimension to European domestic climate policy. In fact, numerous recently adopted legal acts directly or indirectly affect international partners. Nevertheless, the internal and external dimensions of climate policy are not systematically interlinked in the new European Commission, and there is little strategic diplomatic support for the measures. In view of the increased importance of competitiveness and geopolitical constellations, there is an opportunity for a new strategy process. This could help EU institutions and member states coordinate the external dimension and achieve a meaningful advancement of European climate policy.
Keywords: 320; Green Deal; European climate policy; European Union (EU); European Commission; US President Donald Trump; competitiveness; geopolitical constellations; EU Commission President Ursula von der Leyen; Russia's invasion of Ukraine; European Parliament; Carbon Border Adjustment Mechanism (CBAM); Net Zero Industry Act (NZIA); Corporate Sustainability Due Diligence Directive (CSDDD)